2010
DOI: 10.1371/journal.pone.0012743
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Fibroblasts as a Promising Source of Induced Pluripotent Stem Cells

Abstract: BackgroundInduced pluripotent stem (iPS) cells efficiently generated from accessible tissues have the potential for clinical applications. Oral gingiva, which is often resected during general dental treatments and treated as biomedical waste, is an easily obtainable tissue, and cells can be isolated from patients with minimal discomfort.Methodology/Principal FindingsWe herein demonstrate iPS cell generation from adult wild-type mouse gingival fibroblasts (GFs) via introduction of four factors (Oct3/4, Sox2, Kl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(122 citation statements)
references
References 50 publications
2
119
0
1
Order By: Relevance
“…It has also been shown that recombinant laminin E8 fragments (LM-E8s), which are truncated peptides composed of the C-terminal regions of the α, β, and γ chains of laminin, enable robust propagation of human ESCs and iPSCs in an undifferentiated state in cultures with defined and xeno-free media [68]. We have confirmed that human gingiva-derived iPSCs [30] can be maintained in an undifferentiated state on LM-E8-coated plates after dissociation and passaging ( Fig. 12.2).…”
Section: Recombinant Ecm Productssupporting
confidence: 57%
See 1 more Smart Citation
“…It has also been shown that recombinant laminin E8 fragments (LM-E8s), which are truncated peptides composed of the C-terminal regions of the α, β, and γ chains of laminin, enable robust propagation of human ESCs and iPSCs in an undifferentiated state in cultures with defined and xeno-free media [68]. We have confirmed that human gingiva-derived iPSCs [30] can be maintained in an undifferentiated state on LM-E8-coated plates after dissociation and passaging ( Fig. 12.2).…”
Section: Recombinant Ecm Productssupporting
confidence: 57%
“…In contrast to the case with mouse ESCs, LIF does not satisfactorily support the self-renewal of human ESCs [4]. Nonetheless, SNL76/7 cells basically inherit the nature of STO cells; therefore, SNL 76/7 cells can be used as feeder cells for both mouse [6,30,31] and human [1,28,30] ESCs/iPSCs. Bradley also established a puromycin-resistant derivative of SNL76/7 cells (SNLP76/7-4 cell line: Fig.…”
Section: Mouse-derived Feeder Cellsmentioning
confidence: 90%
“…Therefore, iPS cells offer the potential to derive patient-and lineage-specific cells for clinical applications and have emerged as a potential cell source for regenerative medicine and tissue engineering. Previous studies suggested that cell proliferation ability (42,59) or endogenous expression of reprogramming factors (10,55) in parent cells is positively related to the reprogramming efficiency. Human dental pulp cells as parent cells for iPS cells exhibit higher reprogramming efficiency than do human dermal fibroblasts (42,55) because they show rapid cell proliferation (42) and high expression of endogenous reprogramming factors, c-MYC and KLF4 (55), compared to human dermal fibroblasts.…”
Section: Methodsmentioning
confidence: 99%
“…19,20) Briefly, OM cells were seeded into the wells (1 × 10 5 cells /well) of 6-well plates, and were cultured in DMEM with 10% FBS and 1% penicillin-streptomycin at 37°C with 5% CO 2 for 24 h. The (on average, less than 3 weeks). iPS colonies were selected based on mouse ES cell-like colony morphology, and medium was changed every day.…”
Section: Reprogramming Of Mouse Oral Mucosa (Om) Cellsmentioning
confidence: 99%